KONSEP BIWANWISALUS DALAM TARI KURSUS - Toto Sudarto (Greget, 2002)
West Java, dance in recognized by Sudanese dance, one kind of Sudanese in Tan Kursus (Course Dance). Tan Kursus develops from Tayub dance which co//aborted Topeng Cirebon. With in developing of Tan Kursus seems performing art for mans. There are five matters of criteria must be attended for rich of perfectly level for the dancers in Sudanese dance.I would like to study as specially the criteria of danser in kind of Tan Kursus. The criteria are acronym of Biwanwisalus (bisa, wanda, wirahma, sari~ alus). A/us/body coordination: in general skill uses all the body parts, othe,wise to run up the movement of the dance. Wanda/suitable of realizer: the dance structure of reaching of types suitable by the dance with runing up. The type are including costume, make up and dancer body. Wirahma/rasa irama: in on time to cuny of movements rhythm 0/though on time how to understand to ward dance music. Sari/penghayatan: deep understanding of thema and impression for etting energy will accure for the dance to the trough out to became impression wich effected by outsiderhnterpretation ability. Alus/aliran gerak: is throwing down of movement from level to following level withuot accunng difficulty.Key word: Biwanwisalus, Kursus Dance, changes, and developments.